Analisis Kejadian Infeksi Saluran Pernapasan Akut Pada Anak Balita Di Puskesmas Pangkalan Balai Tahun 2023 - Nilawati; Ali Harokan; Chairil Zaman (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2023)
Acute respiratory infections are responsible for nearly 20% of all deaths in children younger than 5 years worldwide. The purpose of this study was to find out the description of the relationship with the incidence of acute respiratory infections in children under five at the Pangkalan Balai District Health Center, Banyuasin Regency in 2023. The design of this study was a quantitative cross-sectional approach. The population in this study were all parents of children under five who visited the Pangkalan Balai Health Center in 2022, namely 4280 respondents. Sampling using slovin theory. The sample in this study amounted to 98 respondents. How to take samples using purposive sampling. This research was carried out on June 6, 2023 to July 6, 2023. Data was collected using a questionnaire. Bivariate data analysis using the Chi-Square test. The results showed that there was a relationship between knowledge (p value 0.016), and smoking (p value 0.001) with the incidence of ARI in children under five at the Pangkalan Balai Health Center, Banyuasin Regency in 2023. There was no relationship between gender (p value 0.685), occupation (p value 5,599) and water sources (p value 1,000) with the incidence of ARI in children under five at the Pangkalan Balai Health Center, Banyuasin Regency in 2023. The conclusion is that there is a relationship between knowledge and smoking, there is no relationship between gender, occupation and water source with the incidence of ARI in children under five at the Pangkalan Balai Health Center in Banyuasin Regency in 2020. It is hoped that health workers will provide counseling about.